The use of medicines in treating hypertension at Thuan Thao clinic in the last 6 months of 2022 - Le, Văn Út; Nguyen, Thị Ánh Tuyết; Tran, Huyền Trân; Nguyen, Phi Long; Tran, Thị Bích Ngọc; Ho , Văn Quốc Huy; Nguyen, Thị Thúy Vân; Lam, Bảo Ngân (Tập san Khoa học và kỹ thuật trường Đại học Bình Dương, 2023)
Hypertension is a common health condition of people in the world as well as in Vietnam, especially the elderly. High blood pressure is a serious cause of health and life expectancy in the community. If a patient with high blood pressure is not properly and adequately treated, it will cause many dangerous complications such as heart attack, angina, blood vessel blockage, heart failure, cerebral ischemia, stroke,... The selection of antihypertensive drugs to ensure rational, safety and effectiveness is always a affair of concern of the medical industry. Therefore, the survey on the use of blood pressure medication in outpatient treatment at Thuan Thao General Clinic in the last 6 months of 2022 was conducted. The results showed that: All antihypertensive drugs surveyed were on the recommended list by Vietnamese Society of Cardiology. Calcium channel blockers and angiotensin receptor blockers are the two most commonly used drug classes (59.57% and 50.7%). The rate of combination of multiple antihypertensive drug in therapy regimen is higher than the rate of using one antihypertensive drug in therapy regimen.